Cooling system for the Resolve onboard XRISM. (June 2020) - Ezoe, Yuichiro; Ishisaki, Yoshitaka; Fujimoto, Ryuichi; Takei, Yoh; Horiuchi, Takafumi; Tsujimoto, Masahiro; Ishikawa, Kumi; Yasuda, Susumu; Yanagase, Keiichi; Shibano, Yasuko; Sato, Kosuke; Kitamoto, Shunji,; et al.
Highlights: We designed the cooling system from room temperature to about 1 K for XRISM Resolve. Based on ASTRO-H (Hitomi) SXS lessons learned, changes on the design are adopted and new tests are planned. The major design changes include an aperture baffle, an eddy current damper and a new vibration isolation system. Abstract: The X-ray Imaging and Spectroscopy Mission (XRISM) is a recovery mission of ASTRO-H (Hitomi) launched in 2016. The Resolve instrument on the XRISM is an 6  ×  6 array of silicon-thermistor microcalorimeters cooled down to 50 mK combined with a 5.6 m focal length X-ray telescope. Its design inherits that of the Soft X-ray Spectrometer (SXS) onboard ASTRO-H that demonstrated high resolution spectroscopy of the X-ray microcalorimeters by observing astronomical objects and providing superb resolution spectra. The cooling chain of the Resolve consists of a 3-stage adiabatic demagnetization refrigerator (ADR), a Joule-Thomson cooler, ~ 30 L superfluid helium, four Stirling coolers and a vacuum vessel or a dewar. Design of the Resolve cooling system is basically the same as that in the SXS but several changes are adopted based on lessons learned. This paper describes mainly the cooling system from room temperature to about 1 K providing the ADR heat sink. Major changes include an aperture baffle for micrometeoroid and orbital debris protection and optical light reduction, an eddy current damper to slow a gate valve opening, a new vibration isolation system with launch-locks.